Relationship Investment and Channel Performance: An Analysis of Mediating Forces - Luo, Yadong; Liu, Yi; Xue, Jiaqi (Journal of Management Studies, 2009)
abstractThis study explores how relationship‐specific investment (RSI) enhances interfirm cooperation in buyer–supplier partnerships in an emerging market. Building upon the logic of economic sociology, we argue that the contribution of RSI to the success in buyer–supplier partnerships will be mediated by reduced opportunism and reduced conflict and by heightened commitment and knowledge sharing. Our survey of 216 paired distributors (buyers) and manufacturers (suppliers) in China generally supports this argument, leading to a conclusion that RSI is not a direct performance propeller but an important builder of relational infrastructure in which mid‐range processes are nourished. Theoretical implications in strategic management and supply chain management research are highlighted.